Blockchain based customer loyalty program in Malaysia apparel industry - Chew, Pek Eng (2024)
This project is a Blockchain-based apparel customer loyalty program design project for academic purposes. The project will provide a more customer-centric customer loyalty program such as more control over their data, secure payment methods, alternative ways of obtaining and using loyalty points, and higher transparency on apparel product information. In traditional customer loyalty programs, customers may face problems such as their data being breached by malicious criminals due to the organization that owned their data has not secured their database well. Also, customers have a high chance of being scammed by online shopping because the funds are directly transferred to the seller's account. Besides, the loyalty points that are owned by customers are bound to the business, which is not flexible and not attractive to customers. Also, the apparel product information is not transparent enough. Although most of the organizations have provided features such as the material used, the sourcing such as labour conditions is still unknown to customers. By implementing Blockchain, these problems can be solved. For the system design, the methodology that will be used in this project is Test Driven Development (TDD), this methodology forces solo developer to define specific test cases before writing code, which helps developer to gain a clear understanding of the requirements and expected behaviour of the project. The hardware involved in this project is a laptop, and software and technologies will be used including Ethereum Sepolia Testnet, Remix IDE, MetaMask, Node.js, Pinata, Firebase, Alchemy, Solidity and Visual Studio Code. The final deliverable of this project is a server-side web application of an apparel customer loyalty program that is enhanced with Blockchain.